An empirical study on attitudes toward gambling when sportswashing is involved - André Syvertsen; André Syvertsen; Eilin Kristine Erevik; Eilin Kristine Erevik; Elise Constance Fodstad; Elise Constance Fodstad; Elise Constance Fodstad; Lisa-Christine Girard; Lisa-Christine Girard; Lisa-Christine Girard; Puneet Kaur; Puneet Kaur; et al. (Frontiers in Psychology, 2023)
Sportswashing is defined as individuals, groups, companies, or countries/regimes’ involvement in sports to improve their own reputation and/or to distract from or normalize wrongdoing. This cross-sectional survey is the first empirical study on sportswashing in relation to gambling. The sample consisted of United Kingdom residents who reported past 12-month gambling (N = 786, 50% women, mean age = 45.6, SD = 15.2). We investigated how many were familiar with sportswashing and their attitudes toward gambling when sportswashing is involved. Exploratory and confirmatory factor analysis (CFA) were conducted on the attitudes scale that was developed for the current study. Multiple regressions were used to examine if individual differences in terms of age, gender, personality, moral foundations, political trust and efficacy, and/or gambling risk were associated with such attitudes. Finally, we examined the percentage of people who avoid gambling on teams/events when sportswashing is involved, including group differences in avoidance and motivations for avoidance according to gambling risk. The results showed that only 32% had heard about sportswashing prior to the survey. CFA indicated that attitudes toward sportswashing and gambling as conceptualized in the scale used in the current study can broadly be categorized into two dimensions: How individuals relate to sportswashing when gambling (“self-factor”) and how individuals think gambling companies and regulators should regulate sportswashing and gambling [an “external-factor,” p < 0.001, CFI = 0.0.996, RMSEA = 0.090, 90% CI (0.077, 0.104)]. Multiple regressions indicated that measures of individual differences explained a significant amount of variance in self-oriented (F (17, 765) = 7.19, p < 0.001, adjusted R2 = 0.12) and external-oriented (F (17, 765) = 8.40, p < 0.001. adjusted R2 = 0.14) attitude toward gambling and sportswashing. Avoidance of betting when sportswashing is involved was reported by 43%. The proportion was lower among those with moderate gambling risk/problem gambling (35%) compared to those with no/low gambling risk (45%). It is concluded that further scale development could help elucidate individual differences in attitudes toward sportswashing and gambling. Sportswashing remains an important social issue, and the present study indicates that this has high relevance for the gambling field.